Sexual Ethics in Pesantren Literature (Sexual Regimentation in Qurrah al-Uyun) - Elya Munfarida; Siti Chamamah Soeratno; Siti Syamsiatun (Institut Agama Islam Negeri Madura, 2017)
The widespread pornography has yielding enormous negative effects for especially women and their born children ranging from diseases, abortion, death, unhealthy sexual life, and so on. These excesses generate from the crisis of sexual ethics that degrade sexual acts as merely for temporary and biological objectives. Using both hermenutics and mainly discourse analysis, this paper seeks to find out the representation of sexual ethics in Qurrah al-‘Uyun and the ways subject being subjectivated in the discourse. This paper finds out that sexual regimentation in Qurrah al-‘Uyun is constituted based on the benefit of sexual act and its danger. The religious and medical precautions are established in order that subjects will follow the recommendations and avoid the cautions to hinder harmful effects the sexual acts may generate for them and their progeny. The goals of sexual acts, favorable times for progeny and pleasure and ritual for sexual acts are so much determined in line with natural, rational and religious arguments. Within this context, they have to apply self restriction and stylizing their sexual behavior according to the determined regimen either alimentary or sexual to gain benefit for future.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1263